2016
DOI: 10.15537/smj.2016.4.13571
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of thyroid, celiac, and anti-cyclic citrullinated peptide autoantibodies coexistence with type 1 diabetes mellitus in patients from Southwestern Saudi Arabia

Abstract: Objectives:To investigate the seroprevalence of coexisting autoantibodies among type 1 diabetes mellitus (T1DM) patients, and to look for possible correlations with age at diagnosis, diabetes duration, and glycemic control.Methods:This is a cross-sectional study conducted at Aseer Central Hospital, Abha, Kingdom of Saudi Arabia from March 2013 to June 2014. A total of 202 T1DM patients were screened for serum anti-thyroglobulin (TG), anti-thyroid peroxidase (TPO), anti-tissue transglutaminase (aTTG), anti-endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…The reported prevalence of CD in the T1DM patients from Saudi Arabia is 10% [20], while 16.4% was reported for Algeria 16.4% [21] and 11% for Iraq [22]. The difference in the prevalence of CD across geographical locations was attributed to the variations in the distribution of the HLA genotypes.…”
Section: Discussionmentioning
confidence: 95%
“…The reported prevalence of CD in the T1DM patients from Saudi Arabia is 10% [20], while 16.4% was reported for Algeria 16.4% [21] and 11% for Iraq [22]. The difference in the prevalence of CD across geographical locations was attributed to the variations in the distribution of the HLA genotypes.…”
Section: Discussionmentioning
confidence: 95%
“…The association between T1DM and celiac disease (CD) was expected, as both the conditions include an increase in the frequency of human leukocyte antigen- (HLA-) DR3 and other HLA [ 67 – 69 ]. However, in most patients, it is often found that CD is diagnosed shortly or sometimes some year after the onset of T1DM [ 70 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Other studies also reported a prevalence of celiac disease in patients with T1DM in Saudi Arabia to be 4.8–11.3% [ 75 ]. Studies conducted from different regions of Saudi Arabia reported that in southern region 10.4%, in central region 11.3%, and in western region 11.2% of patients with T1DM possess celiac disease [ 67 , 69 , 75 ]. It is important to note that a recent study finding shows a high prevalence of celiac disease (19.7%) among TIDM patients in Saudi Arabia [ 51 ].…”
Section: Complicationsmentioning
confidence: 99%
“…40 (7) www.smj.org.sa region (Aseer) (March 2013 and June 2014) and retrospective record based until 2018 in the Southern region (Al-Baha) ( Table 1). [10][11][12][13][14][15][16][17] The pattern of serology and biopsy. Anti-tissue transglutaminase (anti-tTG) was used in 7/8 studies; alone in 4; with anti-endomysium antibody (EMA) in 2; and with anti-gliadin antibody AGA in one.…”
Section: Results Characteristics Of the Patient Studiesmentioning
confidence: 99%
“…7 In the Kingdom of Saudi Arabia, 8,9 the first study 10 concerning the CD in T1DM appeared in 2003, followed by another 7 studies, the last of which was published in 2018. [10][11][12][13][14][15][16][17] The current study represents characterization and meta-analysis for these studies concerned with CD among patients with T1DM in Kingdom of Saudi Arabia.…”
mentioning
confidence: 99%